2020
DOI: 10.1063/5.0015042
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven kinetic energy density fitting for orbital-free DFT: Linear vs Gaussian process regression

Abstract: We study the dependence of kinetic energy densities (KED) on density-dependent variables that have been suggested in previous works on kinetic energy functionals (KEF) for orbitalfree DFT (OF-DFT). We focus on the role of data distribution and on data and regressor selection. We compare unweighted and weighted linear and Gaussian process regressions of KED for light metals and a semiconductor. We find that good quality linear regression resulting in good energy-volume dependence is possible over density-depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 59 publications
(68 reference statements)
2
36
0
Order By: Relevance
“…Similar to what was found with RS-HDMR-GPR in [13], variables x 1 , x 2 , x 3 , x 7 are seen as most important, and their length parameters are relatively small. The importance of x 7 (which is the product of the electron density and Kohn-Sham effective potential) in capturing most of the variance of the KED is also consistent with the result of [22]. The dwindling of the variance of f 4 (x 4 ) and f 5 (x 5 ) corresponds to their optimized length parameters becoming large, indicating their low relevance, in a way similar to ARD.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Similar to what was found with RS-HDMR-GPR in [13], variables x 1 , x 2 , x 3 , x 7 are seen as most important, and their length parameters are relatively small. The importance of x 7 (which is the product of the electron density and Kohn-Sham effective potential) in capturing most of the variance of the KED is also consistent with the result of [22]. The dwindling of the variance of f 4 (x 4 ) and f 5 (x 5 ) corresponds to their optimized length parameters becoming large, indicating their low relevance, in a way similar to ARD.…”
supporting
confidence: 76%
“…The PES data were normalized to unit variance before fitting; we therefore use isotropic kernels. The KED data were scaled to [0,1] for the same reason; as their distributions are extremely uneven (see [22]), we found that scaling is preferred over normalization in this case. The length parameter l is 5.47 (d = 4-6)-8.17 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, in recent years, significant advances in KEF development, including advances in semi-local (i.e. linear-scaling) KEFs [182,183] as well as machine-learned KEFs [194][195][196][197][198][199][200], are being made. The newest functionals appearing in recent years can treat systems with more non-uniform densities and give hope that in relatively near future many materials used in plasmonics (metals as well as non-metals) can be modeled with OFDFT with at least semi-quantitative accuracy.…”
Section: Real-time Td-ofdftmentioning
confidence: 99%
“…Nevertheless, accurate approximations of T s [n] are hard to obtain because this quantity usually gives a dominant contribution to the ground-state energy [3] and because of the highly non-local nature of the KE functional [5,51,[73][74][75][76][77][78]. For this reason, more recently, machine-learning methods have also been used to develop KE functionals [79][80][81][82][83][84][85][86][87].…”
Section: Introductionmentioning
confidence: 99%